Palladium‐Catalyzed Direct Synthesis of Phenanthridones from Benzamides through Tandem N–H/C–H Arylation. Issue 35 (18th September 2017) - Banerji, Biswadip; Chatterjee, Satadru; Chandrasekhar, K.; Nayan, Chinmay; Killi, Sunil Kumar
Abstract : We report a palladium‐catalyzed method for the direct synthesis of phenanthridones from benzamides in a single step. Unlike previous reports, the current protocol does not need any directing groups or any harsh conditions. This methodology has a wide functional group tolerance therefore a series of phenanthridones were synthesized with a yield up to 87 %. The efficacy of this protocol was further explored by synthesizing some important naturally occurring amaryllidaceae alkaloids in a single step with very good yields. Abstract : A palladium‐catalyzed direct synthesis of phenanthridones from benzamides in a single step with yields up to 87 % is reported. The method does not require directing groups or harsh conditions and has a wide functional group tolerance.